2015
DOI: 10.1177/1059840515590607
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services in School-Based Health Centers

Abstract: Mental health issues affect 20-25% of children and adolescents, of which few receive services. School-based health centers (SBHCs) provide access to mental health services to children and adolescents within their schools. A systematic review of literature was undertaken to review evidence on the effectiveness of delivery of mental health services in SBHCs. Databases were searched extensively for research studies published between January 1990 and March 2014. Data analysis was based on the method proposed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 33 publications
4
60
0
3
Order By: Relevance
“…As one example, comprehensive schoolbased health centers are primary medical centers that typically offer integrated preventive, physical, and MH services on school grounds. 34 Prior studies have reported that racial/ ethnic minorities are more likely to receive any MH care 35,36 and receive more MH services at school-based health centers compared with their non-Hispanic white peers. 37 However, these studies have generally been descriptive in nature and more rigorous research is needed on the potential of schoolbased health centers to improve depression care and address racial/ethnic disparities in care in Medicaid-enrolled youth.…”
Section: Discussionmentioning
confidence: 99%
“…As one example, comprehensive schoolbased health centers are primary medical centers that typically offer integrated preventive, physical, and MH services on school grounds. 34 Prior studies have reported that racial/ ethnic minorities are more likely to receive any MH care 35,36 and receive more MH services at school-based health centers compared with their non-Hispanic white peers. 37 However, these studies have generally been descriptive in nature and more rigorous research is needed on the potential of schoolbased health centers to improve depression care and address racial/ethnic disparities in care in Medicaid-enrolled youth.…”
Section: Discussionmentioning
confidence: 99%
“…Given statistics from surveys confirming that women are more prone to experience, or at least report, mental health problems [4, 5, 8] and indications of increased pressure on women to be successful both at home and work [11, 16], the nurses’ perception of girls more frequently experiencing mental health problems could simply reflect reality. However, detailed consideration of the school nurses’ responses and theories on gender suggests that this may be a simplistic interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hagquist [3], mental health problems doubled among adolescent boys and tripled among adolescent girls in Sweden during the years 1988–2005. Moreover, research articles and reviews show that it is a pattern afflicting multiple countries [4, 5]. Frequently, the conditions are associated with recurring pain symptoms, such as headaches, stomach aches, and neck pain [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of mental health treatment these frequent visits have the potential to benefit youth by ensuring safety and stabilization for their mental health condition. Further, prioritizing positive mental health during adolescence promotes academic achievement and may lessen future morbidity …”
Section: Discussionmentioning
confidence: 99%